Characterisation and laboratory investigation of a new ultraviolet multi-wavelength measuring system for high-temperature applications. (June 2016) - Battuello, M.; Girard, F.
Highlights: A novel flexible UV multi-wavelength thermometer was developed and characterised. The UV operation drastically reduce the possible errors of the multi-wavelength approach. A general rule has been developed that confirms the reliability of the results. A result is not guaranteed but when obtained it is with a good level of confidence. Abstract: In the framework of the HiTeMS project of the European Metrology Research Pogramme (EMRP) a new multi-wavelength device for measurement of high temperatures in industrial applications was developed at INRIM. The apparatus takes advantage of the ultra-violet operation with working wavelengths from 350 nm up, which reduces the possible errors connected with the multi-wavelength approach. The instrument has been characterised in terms of optical and electronic behaviour and some laboratory trials were carried out to verify the reliability of the multi-wavelength approach. The true temperature of a blackbody source at 1300 °C with optical windows of unknown spectral transmittance interposed has been defined. By applying an approach that allows a result to be accepted when a threshold limit is reached, it was found that, when an acceptable result can be obtained, errors are comprised within less than 1% of the temperature of the source. Three others single-band thermometers, at 508 nm, 650 nm and an IR broadband 0.8–1.1 μm, were also used to the purpose of a comparison. It has been found that, when the multi-wavelength approach is applicable, it provides generally better or in few cases, at worst similar results of corrected single-wavelength thermometers.